2022
DOI: 10.15584/nsawg.2022.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility (CSR) and sustainable development during the Covid-19 pandemic

Abstract: The coronavirus pandemic affected all areas of social life and changed the conditions in which most industries operate. The current forms of profitable business activities were suspended in many sectors of the market, which forced entrepreneurs to adapt to the new market conditions. During the Covid-19 pandemic, particular attention should be paid to the activities of enterprises in two so far closely related areas: corporate social responsibility (CSR) and sustainable development (SD). Enterprises typically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The developed countries have pledged to assist the demographics most impacted by the COVID-19 outbreak. Kubiczek and Hadasik (2022) opine that CSR projects have grown in number since the Covid-19 pandemic's emergence. This unpredictable epidemiological environment made it more attractive for businesses to participate in social activities.…”
Section: Contextual Propositionsmentioning
confidence: 99%
“…The developed countries have pledged to assist the demographics most impacted by the COVID-19 outbreak. Kubiczek and Hadasik (2022) opine that CSR projects have grown in number since the Covid-19 pandemic's emergence. This unpredictable epidemiological environment made it more attractive for businesses to participate in social activities.…”
Section: Contextual Propositionsmentioning
confidence: 99%
“…It is also worth highlighting that many companies in this period, despite the impacts they suffered, were supportive, and helped society in different ways. In Europe, several initiatives were observed, mainly sewing masks and donating money to fight the pandemic [21]. Some studies have investigated specific types of organisations, for example, Li et al [22] studied CSR practices implemented by football clubs during the COVID-19 pandemic, and found that these activities were an imperative element of building relationships with the club's stakeholders.…”
Section: Introductionmentioning
confidence: 99%